Sociolinguistic Competences, Pragmatic Competences, and Speaking Skills: A Lesson from a Deep Learning Model - Haerazi Haerazi; Lalu Ari Irawan (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study explores the contribution of sociolinguistic and pragmatic competences to the development of preservice English teachers’ speaking skills in an English as a Foreign Language (EFL) context. Speaking competence is not limited to grammatical accuracy, pronunciation, and fluency, but also involves the ability to communicate appropriately and meaningfully according to social context, speaker relationship, politeness, and communicative intention. This study employed a qualitative research design involving 73 EFL preservice teachers enrolled in English Language Education programs at universities in West Nusa Tenggara, Indonesia. Data were collected through interviews designed to investigate participants’ perceptions and experiences related to sociolinguistic competence, pragmatic competence, and speaking development. The data were analyzed using thematic analysis, including data familiarization, coding, theme development, and interpretation. The findings reveal that sociolinguistic competence helps preservice English teachers adjust their spoken language according to context, formality, social roles, and classroom interaction needs. Pragmatic competence enables them to understand implied meanings, speech acts, speaker intentions, and appropriate responses in communication. Together, these competences improve comprehension, expressions, vocabulary, confidence, and the ability to use English appropriately in academic and pedagogical contexts. The study concludes that sociolinguistic and pragmatic competences should be explicitly integrated into English teacher education programs, particularly in speaking courses. This integration can prepare preservice English teachers to become more effective communicators and appropriate language models for their future students.